Penerapan K-Means Dalam Mengelompokkan Nilai Tambah Industri Besar/Sedang Menurut Kabupaten/Kota - Pika Aryani; Ema Meyliza (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
Each region must have industries both primary industries, secondary industries, manufacturing industries, construction industries, service industries and the quarter industry. These industries must produce an output that will be used or consumed by consumers or the public. More and more industries in a region indicates that the region has a lot of market demand from the community and the more industries, the income in the industry of a region increases. In this study the data was taken from a government website namely BPS (Statistics Indonesia) - www.bps.go.id which is a website that presents various statistical data from each region. There are 2 clusters in this study, namely high level clusters (C1) and low level clusters (C2). This study stopped at the 2nd iteration and there were centroid data generated namely high level centroid (78177, 56543, 42610, 155596) and low level centroid namely: ((3513.3), (3448.8), (2390.9) ), (4568)). From the calculation process that has been carried out there are 2 high-level districts / cities namely (Deli Serdang and Medan) and 31 other low-level districts / cities. It is hoped that this research can be input to the government in each region to inform the output data generated from industry in each region, and then the data can be used whenever needed.